1994
DOI: 10.1152/ajpheart.1994.267.6.h2280
|View full text |Cite
|
Sign up to set email alerts
|

Calcium current in rat diabetic ventricular myocytes

Abstract: The magnitude and kinetics of the L-type calcium current were compared in single left ventricular myocytes isolated from 8-mo-old (8M) and 19-mo-old (19M) genetically diabetic rats (WBN/Kob rats) and age-matched control rats. A diabetic state occurred at 19M but not at 8M. The left ventricular contractility was reduced in 19M WBN/Kob rats compared with age-matched control rats. The duration of the action potential was longer in 19M WBN/Kob rats than in the age-matched control rats. Peak inward current density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…I K1 was found unchanged in IDDM [14,[20][21], excluding its contribution to APD prolongation in these animal models of diabetes. I CaL was found smaller in IDMM in some studies [17] but not different in other studies [13,22]. I Na was also found decreased [23].…”
Section: Introductionmentioning
confidence: 64%
“…I K1 was found unchanged in IDDM [14,[20][21], excluding its contribution to APD prolongation in these animal models of diabetes. I CaL was found smaller in IDMM in some studies [17] but not different in other studies [13,22]. I Na was also found decreased [23].…”
Section: Introductionmentioning
confidence: 64%
“…These findings suggest a dysfunction of the intracellular Ca 2+ handling system in the spontaneously diabetic heart, which is likely to include impaired Ca 2+ sequestration and/or extrusion. The WBN/Kob (Wistar Bonn/Kobori) rat is an inbred strain of Wistar rat in which the male rats develop diabetes between the ages of 9 and 15 months [41,42,44]. Tsuchida et al [41] demonstrated abnormal ventricular function in 8 to 19-month-old male WBN/Kob rats, and showed that these rats resemble the NIDDM model, to some extent, in terms of the slow progression of pathophysiological change and a long span without insulin administration.…”
Section: Discussionmentioning
confidence: 99%
“…The WBN/Kob (Wistar Bonn/Kobori) rat is an inbred strain of Wistar rat in which the male rats develop diabetes between the ages of 9 and 15 months [41,42,44]. Tsuchida et al [41] demonstrated abnormal ventricular function in 8 to 19-month-old male WBN/Kob rats, and showed that these rats resemble the NIDDM model, to some extent, in terms of the slow progression of pathophysiological change and a long span without insulin administration. Furthermore, Kakinuma et al [18] investigated the time-course of changes in pancreatic fibrosis in WBN/Kob rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations